2011
DOI: 10.1108/08858621111126992
|View full text |Cite
|
Sign up to set email alerts
|

Suppliers' willingness of customization, effective communication, and trust: a study of switching cost antecedents

Abstract: Purpose - This study seeks to extend current research by testing a framework for understanding the impact of perceived suppliers' willingness for customization, effective communication, and trust regarding perceived switching costs. Design/methodology/approach - Research data were collected from electronics firms in Taiwan; 281 questionnaires were collected. Structural equation model (SEM) analysis was applied to the data. Findings - The study suggests that perceived trust contributes to perceived switching co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 67 publications
2
29
0
1
Order By: Relevance
“…The results of this study also demonstrated positive relationship between brand trust and switching costs supporting the results of the previous studies (Yen et al, 2011;Konuk & Konuk, 2012). In line with this finding, it is infeered that unsuccseesful service recoveries may lead customers switch their current service provider, thus recruiting new customers will bring extra costs for the company (Maxham III, 1999, p.21).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results of this study also demonstrated positive relationship between brand trust and switching costs supporting the results of the previous studies (Yen et al, 2011;Konuk & Konuk, 2012). In line with this finding, it is infeered that unsuccseesful service recoveries may lead customers switch their current service provider, thus recruiting new customers will bring extra costs for the company (Maxham III, 1999, p.21).…”
Section: Discussionsupporting
confidence: 79%
“…Recent evidence revealed positive relationship between trust and switching costs (Yen et al, 2011;Konuk & Konuk, 2012). In other words, brand trust can be attributed as a switching barrier by the customers.…”
Section: Brand Trust and Switching Costsmentioning
confidence: 99%
“…Moreover, while switching costs considerations have been studied in MIS research, they have not been tied to trust aspects. Trust is an important determinant of such switching cost assessments [49]. Hence, integrating these concepts in the context of IS use is beneficial.…”
Section: Social Investment In the Context Of Social Networking Websitesmentioning
confidence: 99%
“…The supplier may design a specific marketing strategy to respond to the pressure from its main competitors, such as the determination of product variety, price reductions, and market expansion share (Prior, 2012). Before the marketing strategy is executed the marketing division should first communicate with the retailer or customer (Yen, Wang, & Horng, 2011). Frequently, suppliers revise their strategies if they encounter resistance in the early stages of the socialization of the marketing strategies.…”
Section: Network Synergy Capacitymentioning
confidence: 99%